Presencia de la mujer y brecha de género en la política local española - Espí-Hernández, Alejandro (FEMERIS: Revista Multidisciplinar de Estudios de Género, 2017)
This article analyses in quantitative and qualitative terms the current presence of women in the Spanish local administration with a temporary comparated perspective. With the analysis and the interpretation of different data, we try to observe the historical evolution and the actual state of gender parity in the Spanish local administration. In the same way, we pretend to verify if legal and organic actions leading to correct gender imbalances are improving the representation of women in local power. The present work is also interested in knowing the role of women, regarding men, once they have assumed local public responsibility. In order to achieve all of these aims, we analyse external aspects (mainly concerning councils and mayors), as well as internal ones (distribution of positions and thematic areas, as well as internal promotion of women) which project a compared view of the situation of women and men in the Spanish local administration since they have data. These variables will allow us to argue precise conclusions about the equality, or absence of it, within those public administrations that are considered the closest ones to citizenship. The interpretation of the data, mainly the external ones, shows us a positive evolution in the number of councilors and, at the same time, a strong resistance in the figure of the mayor’s office. On the other hand, the internal data alert us about the existence of an inequality and reproduction of the gender roles within the own municipalities.